Draft Five Year Plan 1978-83 Rural Housing Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
In order to ensure the active participation of the allottees in construction of houses and development of the area and provision of basic amenities, it is necessary that the labour component be provided by the allottees and their families themselves. The wages could be paid to them in kind under the " food for work programme ", Annexure II gives the details required under each head during the plan period.
Government of Madhya Pradesh, Planning, Economics and Statistics Department